Study of Corn Plant Availability as a Source of Forage for Feed and Beef Cattle Waste Potential - Paramuji, Muji; Suprihatin; Sunarti, Titi Candra; Sukard (Jurnal Online Pertanian Tropik, 2020)
ABSTRACT One of the factors that determine the growth of beef cattle is the supply of feed. The main feed source for beef cattle is forage which is currently increasingly limited in availability. The purpose of this study is to examine and evaluate the utilization of corn waste into forage sources of feed and the potential amount of beef cattle waste in Deli Serdang Regency. The data source used in this study is secondary data covering the planting area of corn and beef cattle population described in a qualitative description. The results of studies and evaluations indicated that the availability of forage production of corn (stover) as a source of forage for beef cattle feed in Deli Serdang Regency, in average is only sufficient of 80.57% of the existing beef cattle population, that is every 20,066.95 Ha of corn plants can provide forage for 75,234 cows. Cattle waste potential in the form of feces is 509,385,066.00 kg/year, urine is 203,479,979.00 L/year and the remaining feed is 34,255,889.00 kg/year. Keywords: corn, forage, feed, beef cattle